Editorial - Mattos, Amana; Souza, Alice De Marchi Pereira de; Jacó Vilela, Ana Maria; Mendonça, Anderson Pereira; Mendes, Deise Maria Leal Fernandes; Ponciano, Edna Lúcia Tinoco; Degani-Carneiro, Filipe; Ribeiro, Heloisa Fernandes Caldas; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; et al. (Estudos e Pesquisas em Psicologia, 2021)
Alice De Marchi Pereira de Souza, Amana Mattos, Ana Maria Jacó Vilela, Anderson Pereira Mendonça, Deise Maria Leal Fernandes Mendes, Edna Lúcia Tinoco Ponciano, Filipe Degani-Carneiro, Heloisa Fernandes Caldas Ribeiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Luiz Fernando Tura, Marcos Vinicius Brunhari, Patrícia Lorena Quitério, Rosana Lazaro Rapizo, Vitor Castro Gomes